Diagnostic Yield of Cytogenomic Abnormalities in Current Prenatal Diagnosis: A Retrospective Analysis in a Clinical Cytogenetics Laboratory - Li, PhD, Peining; DiAdamo, BS, Autumn; Grommisch, BS, Brittany; Boyle, MS, Jennifer; Amato, BS, Katherine; Wang, MS, Dongmei; Chai, PhD, MD, Hongyan (North American Journal of Medicine and Science, 2016)
Background: Chromosome microarray analysis has been the first-tier genetic testing for pediatric patients and an integrated testing for prenatal cases. Aims: The purpose of this study was to evaluate the diagnostic yield from current prenatal genetic clinics and to provide guidance for future improvement on prenatal diagnosis of cytogenomic abnormalities. Material and Methods: A retrospective analysis of abnormal findings from karyotyping and array comparative genomic hybridization (aCGH) analysis of amniotic fluid (AF) specimens and chorionic villi samples (CVS) during the 2012-2015 interval was performed. The diagnostic efficiency as determined by the relative frequencies (RF) of different types of cytogenomic abnormalities was compared between prenatal and pediatric case series. Result: Data retrieved from this four-year interval presented 341 AF and 656 CVS with an annual caseload of 249 cases and an abnormality detection rate (ADR) of 20.2%. A comparison with prenatal testing performed in the 2007-2009 interval noted a 57% reduction of annual caseload and a 67% increase in ADR. While the ADR for structural chromosomal abnormalities remained the same; it was estimated that 80% of the increased ADR resulted from improved detection of numerical chromosomal abnormalities and 20% were from submicroscopic genomic aberrations detected by aCGH analysis. The RF for numerical chromosome abnormalities, structural chromosomal abnormalities, microdeletion and microduplication syndromes, and other genomic aberrations were 83.5%, 9%, 3.5% and 4% for the prenatal cases and 8.5%. 9.7%, 37.5% and 44.3% for a pediatric case series, respectively. Similar frequency in the detection of structural chromosomal abnormalities and striking different frequencies in other types of abnormalities were noted. Conclusion: These results indicated that the current prenatal diagnosis is effective in detecting chromosomal abnormalities but has a limitation on detecting genomic aberrations. Better correlations of ultrasonagraphic fetal anomalies and maternal serum fetal DNA quantitation with genomic aberrations are needed to improve prenatal cytogenomic analysis. [N A J Med Sci. 2016;9(4):136-140. DOI: 10.7156/najms.2016.0904136] Key Words: prenatal diagnosis, array comparative genomic hybridization, chromosomal abnormalities, microdeletion/duplication syndromes, pathogenic copy number variants, diagnostic yield